Theoretical Basis Of The Teaching And The Character Of Makeover In The Formation Of Neologisms (The Peerian Journal, 2024)
The using of neologisms can be start in many courses of theme such as in the economic, medicinal, discipline and skill and also in the family’s literature. Neologisms is measured as the major interpreter problem while doing a translation procedure because there are many arguments which cannot be found in the vocabulary although the meaning of it is familiar. Nowadays, the number of it has augmented steeply because of the broadcasting, writers, educators or even a municipal figure. The internet has also created for numbers of neologisms such as the using of prefix e- in e-mail, e-business, e-commerce etc. The term neologisms originally come from Greek vἐo- néo which means “new” and λὀɣoς- lὀgos which means “speech or utterance”. Neologisms are possibly the non-literary and the professional translator's biggest problem. New object and processes are continually created in technology. New ideas and variations on feelings come from the media. Terms from the social sciences, slang, dialect coming into the mainstream of language transferred words, make up the rest. A few years ago, three hundred “words” were said to be calculated in four successive numbers of the French weekly language rapid. It has been stated that each language acquires three thousand new words annually. In fact, neologisms cannot be enumerated, since so many hover between reception and unconsciousness and many are short-lived individual citations